EXPLORING LEXICAL COMPLEXITY IN SCIENTIFIC WRITING: A CORPUS-BASED STUDY ACROSS DISCIPLINES - Ayadi, Mouna (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study examines the lexical complexity of scientific writing. It specifically focuses on the degree of lexical density and lexical diversity in the results and discussion sections of research articles. Using a qualitative approach with quantification to back it up, this study scrutinized 60 results and discussion sections of research articles written by Tunisian linguistics and engineering scholars. The analysis was conducted using the lexical complexity analyzer developed by Lu (2010). Moreover, descriptive analysis and the independent T-test were conducted to ascertain the statistical distinctions between the discussion and results sections of linguistics and engineering disciplines. The findings suggest that engineering scholars wrote in a more concise and information-dense style, with a greater lexical density, while linguistics scholars used a broader range of linguistic forms, resulting in more diverse and richer expressions. The differences in writing style can be attributed to the nature of the disciplines and the types of research conducted within each field. The results obtained from this study may offer valuable implications for English for Academic Purposes (EAP) writing instructions.